Health Literacy in the Short Film Stunting “Konsumsi Bergizi Bikin Glowing” - Rifaqi, Dela Aufa; Adiprabowo, Vani Dias (International Journal of Science and Society, 2024)
Indonesia is a developing country with a low health index, one of which is indicated by the high prevalence of stunting. Stunting is a growth disorder in children due to chronic malnutrition that has an impact on long-term physical and cognitive health. This study aims to explore the messages in the short film "Nutritious Consumption Makes You Glowing" produced by the DIY Health Service in improving adolescent health literacy related to preventing stunting through the consumption of nutritious food and blood-boosting supplements. Using a qualitative approach, this study analyzed the content of the film and relevant literature. The results showed that this film succeeded in conveying health literacy effectively through direct socialization carried out by Bu Bidan. Messages about the importance of balanced nutrition and blood supplementation are conveyed in a way that is easy for adolescents to understand and accept. Scenes in the film depict changes in healthy lifestyles that are starting to be adopted by adolescents, showing that education through audiovisual media can influence people's nutritional behavior and awareness. Thus, this short film is an effective educational tool in improving health literacy and preventing stunting among adolescents.